A Bottomside Parameterization for the Empirical Canadian High Arctic Ionospheric Model. Issue 5 (7th May 2019) - Themens, David R.; Jayachandran, P.T.; McCaffrey, Anthony M.; Reid, Benjamin; Varney, Roger H.
Abstract: In this study, we present a bottomside model representation to be used by the Empirical Canadian High Arctic Ionospheric Model (E‐CHAIM). This model features a new approach to modeling the bottomside electron density; namely, instead of modelling electron density directly, E‐CHAIM models the altitude profile of the scale thickness of a single bottomside layer. In this approach, the curvature in the bottomside associated with the E region and F 1 layer is represented in the scale thickness domain as a peak function centered at the layer peak altitude. The use of this approach ensures the production of explicitly doubly differentiable bottomside electron density profiles and directly avoids issues known to exist within current standards, such as the International Reference Ionosphere (IRI), which has discontinuities in space, time, and in the vertical electron density gradient. In terms of performance, after removing the impacts of hmF 2 and NmF 2, the new E‐CHAIM profile function generally performs comparably to the IRI, with bottomside TEC from both models within 2.0 TECU (1 TECU = 10 16 e/m 3 ) of observations. More specifically, the E‐CHAIM bottomside is demonstrated to outperform the IRI bottomside function in the F region during low solar activity periods with respect to incoherent scatter radar observations. At high latitudes, E‐CHAIM tends to outperform the IRI during winter months by between 10% and 40% of NmF 2 while being outperformed by the IRI by between 10% and 25% of NmF 2 during summer periods, mainly during the daytime at high solar activity. Key Points: A bottomside function for the Empirical Canadian High Arctic Ionospheric Model (E‐CHAIM) is presented The IRI demonstrates electron density discontinuities in space, time, and in its vertical gradients The E‐CHAIM bottomside function performs comparably to the IRIs while avoiding the need for discontinuous behavior and ensuring continuous derivatives